Sclerostin is expressed in osteoclasts from aged mice and reduces osteoclast‐mediated stimulation of mineralization12. Issue 8 (12th June 2013) - Ota, Kuniaki; Quint, Patrick; Ruan, Ming; Pederson, Larry; Westendorf, Jennifer J.; Khosla, Sundeep; Oursler, Merry Jo
Abstract Osteoclast‐mediated bone resorption precedes osteoblast‐mediated bone formation through early adulthood, but formation fails to keep pace with resorption during aging. We previously identified several factors produced by osteoclasts that promote bone formation. In this study, we determined if osteoclast‐produced factors contribute to the impaired bone formation with aging. We previously found that mice between the ages of 18 and 22 months develop age‐related bone loss. Bone marrow‐derived pre‐osteoclasts were isolated from 6‐week, 12‐month, and 18‐ to 24‐month‐old mice and differentiated into osteoclasts in vitro. Conditioned media were collected and compared for osteoblast mineralization support. Conditioned medium from osteoclasts from all ages was able to support mineralization of bone marrow stromal cells. Concentrating the conditioned medium from 6‐week‐old and 12‐month‐old mouse marrow cells‐derived osteoclasts enhanced mineralization support whereas concentrated conditioned medium from 18‐ to 24‐month‐old mouse marrow‐derived osteoclasts repressed mineralization compared to base medium. This observation suggests that an inhibitor of mineralization was secreted by aged murine osteoclasts. Gene and protein analysis revealed that the Wnt antagonist sclerostin was significantly elevated in the conditioned media from 24‐month‐old mouse cells compared to 6‐week‐old mouse cells. Antibodies directed to sclerostin neutralized the influences of the aged mouse cell concentrated conditioned media on mineralization. Sclerostin is primarily produced by osteocytes in young animals. This study demonstrates that osteoclasts from aged mice also produce sclerostin in quantities that may contribute to the age‐related impairment in bone formation. J. Cell. Biochem. 114: 1901–1907, 2013. © 2013 Wiley Periodicals, Inc.